2012
DOI: 10.1021/ja303154g
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solvent Additives on Morphology and Excited-State Dynamics in PCPDTBT:PCBM Photovoltaic Blends

Abstract: The dependence of the thin film morphology and excited-state dynamics for the low-bandgap donor-acceptor copolymer poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b']-dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (PCPDTBT) in pristine films and in blends (1:2) with [6,6]-phenyl-C(61)-butyric acid methyl ester (PCBM) on the use of the solvent additive 1,8-octanedithiol (ODT) is studied by solid-state nuclear magnetic resonance (NMR) spectroscopy and broadband visible and near-infrared pump-probe trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
227
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(263 citation statements)
references
References 56 publications
29
227
1
1
Order By: Relevance
“…[9][10][11]13,17,41 We are not able to distinguish charges that are bound in the CT state from free ones using the broad polaron absorption band (similar spectral signatures have also been noted in TA studies of some other polymers). 9,10 On the basis of a model by Laquai et al, 9−11 both are expected even at the earliest time delays, since they are instantaneously generated and do not interconvert. A recent pump-push photoconductivity experiment confirms that free charge carriers are generated from "hot" delocalized states populated directly following CS.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…[9][10][11]13,17,41 We are not able to distinguish charges that are bound in the CT state from free ones using the broad polaron absorption band (similar spectral signatures have also been noted in TA studies of some other polymers). 9,10 On the basis of a model by Laquai et al, 9−11 both are expected even at the earliest time delays, since they are instantaneously generated and do not interconvert. A recent pump-push photoconductivity experiment confirms that free charge carriers are generated from "hot" delocalized states populated directly following CS.…”
mentioning
confidence: 54%
“…A similar flat band extending next to the GSB with a peak at lower wavelengths has been observed in blends of other donor− acceptor copolymers with PCBM, and was also assigned to the charged polymer. 9,17 The anion of PCBM is known to absorb in the 1030 nm region, and is thus outside our measuring window. 13 It has often been reported that CS occurs quantitatively in less that 100 fs in polymer:fullerene bulk heterojunctions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…40,59 However, the presence of these domains also plays a key role in reducing geminate and non-geminate charge recombination losses within the blend, as we discuss below, such that optimum device performance is achieved at higher (1:3 or 1:4) blend ratios. After concluding that polymer excitons are efficiently separated in all SiIDT-DTBT:PC70BM…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] To improve the photovoltaic performance of OPVs, morphology and charge transport in bulk heterojunction (BHJ) solar cells are important. Many methods were used to optimize the morphology of polymers and fullerenes in BHJ such as thermal annealing [4,5], solvent annealing [6,7] and addition of solvent additives [8,9]. One effective method to control the morphology of polymer-fullerene is adding high boiling point additive in polymer blend such as 1,8-diiodooctane (DIO) [10], 1,8-dibromooctane [11] and chloronaphthalene [12].…”
Section: Introductionmentioning
confidence: 99%